Alternative treatments for chronic spontaneous urticaria beyond the guideline algorithm - Vena, Gino A; Maurer, Marcus; Cassano, Nicoletta; Zuberbier, Torsten (Current opinion in allergy and clinical immunology, 2017)
The international EAACI/GALEN/EDF/WAO guideline suggests a stepwise approach for the therapeutic management of chronic spontaneous urticaria (CSU), outlined in an algorithm. The aim of this article is to summarize and review the evidence available on alternative treatment options for CSU outside of this algorithm. Although CSU is a common disease, there are a limited number of high-quality studies, and only antihistamines and omalizumab are licensed for its treatment. Most studies regarding alternative therapies for CSU show methodological limitations and a high risk of bias. For many therapies, only case reports and uncontrolled studies exist. Recent publications on alternative treatments for chronic urticaria/CSU include reports on the use of adalimumab, rituximab, vitamin D, probiotics, histaglobulin, injection of autologous whole blood or serum, and phototherapy. Numerous treatments beyond the guideline algorithm have been evaluated in patients with refractory CSU. The global level of evidence to support their efficacy in CSU is low or very low. Further research is needed to assess the efficacy and safety of alternative therapies of CSU to manage adequately those patients who do not respond to the treatments included in the algorithm.